To select a component for solar power plant with stirling engines - Zhukeshov, A.M.; Koval, N.N.; Amrenova, A.U.; Gabdullina, A.T.; Mukhamedryskyzy, M. (Recent Contributions to Physics, 2014)
The article discusses the development of resource-saving, environmentally friendly technologies for creating products of structural and tool steels and alloys with given properties of surface. This effect can be achieved using pulsed plasma systems and electron beam treatment, which are more effective and manufacturable than the stationary systems. In the result will be formed layers comprising intermetallic, carbide and nitride phases that are changing the depth of the nanocrystalline structure on the surface to a depth submicrocrystalline. The using plasma and electron accelerators resulting surface material nanostructured, are unique and can achieve several times higher strength properties and service life of the products compared with traditional technologies (hardness 50 GPa) and can not be obtained in other ways. Industrial testing showed that after the operation of modifying the working surfaces of tools and machine parts is increased in 3 ... 5 times. The technology can be used in all areas that require extra strong surface properties of materials, from engineering to the space industry.